Review of current 2SLGBTQIA+ inequities in the Canadian health care system - Comeau, Dominique; Johnson, Claire; Bouhamdani, Nadia (Frontiers in Public Health, 2023)
Gender identity and sexual orientation are determinants of health that can contribute to health inequities. In the 2SLGBTQIA+ community, belonging to a sexual and/or gender minority group leads to a higher risk of negative health outcomes such as depression, anxiety, and cancer, as well as maladaptive behaviors leading to poorer health outcomes such as substance abuse and risky sexual behavior. Empirical evidence suggests that inequities in terms of accessibility to health care, quality of care, inclusivity, and satisfaction of care, are pervasive and entrenched in the health care system. A better understanding of the current Canadian health care context for individuals of the 2SLGBTQIA+ community is imperative to inform public policy and develop sensitive public health interventions to make meaningful headway in reducing inequity. Our search strategy was Canadian-centric and aimed at highlighting the current state of 2SLGBTQIA+ health inequities in Canada. Discrimination, patient care and access to care, education and training of health care professionals, and crucial changes at the systemic and infrastructure levels have been identified as main themes in the literature. Furthermore, we describe health care-related disparities in the 2SLGBTQIA+ community, and present available resources and guidelines that can guide healthcare providers in narrowing the gap in inequities. Herein, the lack of training for both clinical and non-clinical staff has been identified as the most critical issue influencing health care systems. Researchers, educators, and practitioners should invest in health care professional training and future research should evaluate the effectiveness of interventions on staff attitudinal changes toward the 2SLGBTQIA+ community and the impact on patient outcomes.